A readout digitization system for the ATLAS muon spectrometer phase-I tRPC trigger upgrade. (24th October 2017) - Meng, X.T.; Levin, D.S.; Chapman, J.W.; Li, D.C.; Yao, Z.E.; Zhou, B.
Abstract: The front-end digitization electronics for thin-Resistive Plate Chambers to be installed as part of the ATLAS Muon Spectrometer Phase-I upgrade project is described. The design is based on the CERN HPTDC and GOL chips. In this paper, the design of the digitization system is presented, including power, connection interfaces to front-end amplifier-shaper-discriminator board and to the low level trigger processor board. System performance tests were conducted and validated with a prototype which includes one HPTDC/GOL pair.